Resistance of hypervirulent Klebsiella pneumoniae to cathepsin B-mediated pyroptosis in murine macrophages - Kim, Jin Kyung; Jung, Hui-Jung; Hyun, Miri; Lee, Ji Yeon; Park, Jong-Hwan; Suh, Seong-Il; Baek, Won-Ki; Kim, Hyun ah (Frontiers in Immunology, 2023)
Introduction: Hypervirulent Klebsiella pneumoniae (hvKp) has emerged as a clinically significant global pathogen in the last decade. However, the host immune responses of the macrophages during hvKp infection are largely unknown. In the present study, we aimed to compare the cytotoxic effects of hvKp and classical K. pneumoniae (cKp) in murine macrophages. Results: We found that the activation of caspase-1 (Casp1)-dependent pyroptosis was higher in cKp-infected macrophages compared with that in hvKp-infected macrophages. In caspase-1 deficiency macrophages, pyroptosis diminished during infection. Both hvKp and cKp strains led to nucleotide-binding and oligomerization domain-like receptor protein 3 (NLRP3) inflammasome formation and lysosomal cathepsin B activation, thus resulting in pyroptosis. Compared with the cKp strain, the hvKp strain inhibited these phenomena in murine macrophages. Conclusions: HvKp infection resulted in different levels of pyroptosis via the activation of cathepsin B-NLRP3-caspase-1 in murine macrophages. Therefore, the manipulation of pyroptotic cell death is a potential target for host response during hvKp infection in macrophages.